(untitled) (American Journal of Islam and Society, 2019)
The Muslim Brotherhood is considered to be the most significant and effective Islamic revivalist organization; or, in the words of Milton-Edwards, “a complex, far-reaching, and dynamic expression of contemporary Islamism” (188). Started as a movement to resist or oppose the Westernization of Muslim society, particularly Egyptian society, it spread quite rapidly within and beyond Egypt, inspiring a huge number of Muslims in various parts of the Muslim world and achieving, thus, the status of a global movement.